Patterns of retinal damage facilitate differential diagnosis between Susac syndrome and MS. - Alexander U Brandt (Public Library of Science (PLoS), 2012)
Susac syndrome, a rare but probably underdiagnosed combination of encephalopathy, hearing loss, and visual deficits due to branch retinal artery occlusion of unknown aetiology has to be considered as differential diagnosis in various conditions. Particularly, differentiation from multiple sclerosis is often challenging since both clinical presentation and diagnostic findings may overlap. Optical coherence tomography is a powerful and easy to perform diagnostic tool to analyse the morphological integrity of retinal structures and is increasingly established to depict characteristic patterns of retinal pathology in multiple sclerosis. Against this background we hypothesised that differential patterns of retinal pathology facilitate a reliable differentiation between Susac syndrome and multiple sclerosis. In this multicenter cross-sectional observational study optical coherence tomography was performed in nine patients with a definite diagnosis of Susac syndrome. Data were compared with age-, sex-, and disease duration-matched relapsing remitting multiple sclerosis patients with and without a history of optic neuritis, and with healthy controls. Using generalised estimating equation models, Susac patients showed a significant reduction in either or both retinal nerve fibre layer thickness and total macular volume in comparison to both healthy controls and relapsing remitting multiple sclerosis patients. However, in contrast to the multiple sclerosis patients this reduction was not distributed over the entire scanning area but showed a distinct sectorial loss especially in the macular measurements. We therefore conclude that patients with Susac syndrome show distinct abnormalities in optical coherence tomography in comparison to multiple sclerosis patients. These findings recommend optical coherence tomography as a promising tool for differentiating Susac syndrome from MS.